2022
DOI: 10.1109/access.2022.3215504
|View full text |Cite
|
Sign up to set email alerts
|

TIPS: Transformer Based Indoor Positioning System Using Both CSI and DoA of WiFi Signal

Abstract: In a channel state information (CSI) based indoor positioning system, the positioning performance becomes susceptible to multipath fading effects especially in non-line-of-sight environments. We propose a transformer-based indoor positioning system (TIPS) to address this challenge. The proposed TIPS utilizes a self-attention mechanism to process the continuous WiFi CSI observed from predetermined routes as fingerprints in a given indoor environment. Each route is then considered a sentence, whereas the positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…We compared the Euclidean distance error using existing commercialized machine learning algorithms and displayed the results in Fig. 10, which suggests the feasibility of the [41,42,43,44].…”
Section: ) Indoor Localization Errorsmentioning
confidence: 96%
“…We compared the Euclidean distance error using existing commercialized machine learning algorithms and displayed the results in Fig. 10, which suggests the feasibility of the [41,42,43,44].…”
Section: ) Indoor Localization Errorsmentioning
confidence: 96%
“…Frequency Identification (RFID), Bluetooth, WiFi fingerprinting, etc. Recently, [3], [9] has shown that WiFi with channel state information can be utilized for Indoor Positioning System (IPS) and have the same positioning cost and its accuracy is not inferior to UWB. Non-line-of-sight (NLoS) conditions are a major hindrance in achieving high positioning accuracy [10], [11].…”
Section: Beside This Various Alternative Technologies Have Been Exten...mentioning
confidence: 99%
“…Methods such as Deep Neural Networks (DNN), Convolutional Neural Networks (CNN), Recurrent Neural Networks (RNN) and Long-Short Term Memory (LSTM) have been extensively tested by the DL community [5]. The Transformer network [6] offers several advantages over other sequence-processing neural networks like Recurrent Neural Networks (RNN) [7] and Long-Short Term Memory (LSTM) [8] and has been effectively deployed in applications for natural language processing [9,10,11], computer vision [12], and tested for indoor localization using CSI [13,14]. The Transformer uses an attention mechanism to capture pairwise relationships while effectively learning long-range dependencies in the input.…”
Section: Introductionmentioning
confidence: 99%